Hijab as Moral Pedagogy: A Comparative Study of Classical And Contemporary Qur’anic Exegesis from A Character Education Perspective - Gifari, Buyung Al; Bin salman, Abdul Matin (Pascasarjana Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga, 2025)
This study examines the obligation of hijab through the lens of character education by comparatively analyzing the interpretations of classical and contemporary Muslim scholars. Employing a qualitative comparative-analytical library research design, the study analyzes key Qur’anic verses on hijab alongside authoritative classical and modern tafsir works to explore their normative, ethical, and pedagogical dimensions. The findings reveal a fundamental continuity between classical and contemporary scholars regarding the obligatory status of hijab as grounded in the Qur’an and Sunnah, while also demonstrating a significant shift in interpretative emphasis. Classical exegesis primarily adopts a textual-normative approach focused on legal obligation, bodily coverage, and social protection within early Islamic contexts. In contrast, contemporary interpretations extend this framework by emphasizing character formation, spiritual consciousness, moral agency, identity construction, and contextual adaptability in modern societies. The study further identifies core character education values embedded in the hijab discourse, including obedience, modesty, self-dignity, piety, self-discipline, social responsibility, and ethical identity. These values position hijab as an integrative moral practice rather than a purely formalistic or symbolic requirement. The implications of this research highlight the potential of integrative exegesis to inform inclusive, empowering, and context-sensitive Islamic education that frames hijab as a meaningful ethical choice. The study is limited by its textual focus and lack of empirical investigation. Future research is recommended to incorporate lived experiences, educational practices, and interdisciplinary perspectives to enrich contemporary hijab discourse.